Is the Relationship between Race and Continuous Positive Airway Pressure Adherence Mediated by Sleep Duration? - Billings, Martha E.; Rosen, Carol L.; Wang, Rui; Auckley, Dennis; Benca, Ruth; Foldvary-Schaefer, Nancy; Iber, Conrad; Zee, Phyllis; Redline, Susan; Kapur, Vishesh K. (Sleep (New York, N.Y.), 2013)
Black race has been associated with decreased continuous positive airway pressure (CPAP) adherence. Short sleep duration, long sleep latency, and insomnia complaints may affect CPAP adherence as they affect sleep and opportunity to use CPAP. We assessed whether self-reported sleep measures were associated with CPAP adherence and if racial variations in these sleep characteristics may explain racial differences in CPAP adherence. Analysis of data from a randomized controlled trial (HomePAP), which investigated home versus laboratory-based diagnosis and treatment of obstructive sleep apnea. Seven American Academy of Sleep Medicine-accredited sleep centers in five cities in the United States. Enrolled subjects (n = 191) with apnea-hypopnea index ≥ 15 and sleepiness (Epworth Sleepiness Scale > 12). N/A. Multivariable regression was used to assess if subjective sleep measures and symptoms predicted 3-mo CPAP use. Mediation analysis was used to assess if sleep measures mediated the association of race with CPAP adherence. Black participants reported shorter sleep duration and longer sleep latency at baseline than white and Hispanic participants. Shorter sleep duration and longer sleep latency predicted worse CPAP adherence. Sleep duration mediated the association of black race with lower CPAP adherence. However, insomnia symptoms were not associated with race or CPAP adherence. Among subjects with similar severity of obstructive sleep apnea and sleepiness, baseline self-reported sleep duration and latency, but not perceived insomnia, predicted CPAP adherence over 3 mo. Sleep duration explains some of the observed differences in CPAP use by race. Sleep duration and latency should be considered when evaluating poor CPAP adherence. PORTABLE MONITORING FOR DIAGNOSIS AND MANAGEMENT OF SLEEP APNEA (HOMEPAP) URL: http://clinicaltrials.gov/show/NCT00642486. NIH clinical trials registry number: NCT00642486.